2018
DOI: 10.4274/jpr.24471
|View full text |Cite
|
Sign up to set email alerts
|

Determining Risk Factors of Epilepsy in Children with Cerebral Palsy: A Retrospective Study

Abstract: were evaluated retrospectively. The diagnosis of CP was based on the definition of motor dysfunction caused by a non-progressive, static lesion in the developing brain (6). The patients were classified according to their gestational age (GA) and birthweight (BW) for GA (7). Newborns who were born prior to 37 weeks and between 37 and 42 weeks were accepted as preterm and term babies, ABS TRACT Aim: The aim of this study is to determine the risk factors of epilepsy development in children with cerebral palsy. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
4
1
0
1
Order By: Relevance
“…Similar to previous reports, the onset of epilepsy in the current study occurred at a young age (13 months) and more than half of our patients had their first seizures during the first two years of life (11,16). In addition, the median age of seizureonset was earlier in patients with DRE (7 months) than in the controlled epilepsy group (24 months).…”
Section: Methodssupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to previous reports, the onset of epilepsy in the current study occurred at a young age (13 months) and more than half of our patients had their first seizures during the first two years of life (11,16). In addition, the median age of seizureonset was earlier in patients with DRE (7 months) than in the controlled epilepsy group (24 months).…”
Section: Methodssupporting
confidence: 91%
“…In the current study, there was no significant difference between patients with and without epilepsy in terms of sex, parental consanguinity, and mode of delivery (p>0.050). Similar to our results, Gurkan et al (11) found no significant association between epilepsy development and history of NICU hospitalization. In our study, six of seven patients with a history of neonatal hypoglycemia had epilepsy during follow-up.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pediatrik SP'liler ile yapılan çalışmalarda epilepsi prevalansı %15 ila %60 arasında değişen oranlarda görülmektedir 16,17 . Ülkemizde Gürkan ve arkadaşlarının çalışmasında ise bu oran %50 olarak bulunmuştur 18 . Çalışmada ise epilepsi oranı %60 saptanmış olup, bu oranın literatüre göre yüksek olduğu görülmektedir.…”
Section: Discussionunclassified
“…According to the data from the Central Statistics Agency, the percentage of malnutrition in children, especially in Gunung Kidul, was 0.53%, and malnutrition was 6.55% (Badan Pusat Statistik, 2019). Seizures were common in children with Cerebral Palsy with rates varying from 15 percent to 60 percent (Gürkan, et al, 2018) (mostly the mothers of children with Cerebral Palsy), the caregivers wanted to learn and know how to meet the nutrition requirement for children with CP, symptoms that could affect the children's condition, medications advised for managing digestive system disorders. There were limited services related to Cerebral Palsy and there was no pediatrician at the nearest community health center (Puskesmas).…”
Section: Introductionmentioning
confidence: 99%